The Case for Molybdenum in ALS Therapy - Gelbard, Amos (British Journal of Healthcare and Medical Research, 2025)
Amyotrophic lateral sclerosis (ALS) is a devastating disease without a known cure or cause, herein 3 studies will be presented that all somehow contribute to the possibility of Molybdenum, a chemical element with the atomic number 42 is what’s missing in ALS patients diet leading to their disease, that at least according to one study done mostly on animals. Both other studies mentioned Molybdenum only as an afterthought, on a list of many vitamins and minerals contributing to their interventions. Both studies who used Molybdenum showed decisive results with one study reporting the thorough healing of an ALS patient and the other, with much lower levels of Molybdenum per intervention resulted in much better mortality rates in the intervention group. Brought together these finding warrant further study of Molybdenum’s possible therapeutic role in intervention for ALS.